The fate and enantioselective behavior of zoxamide during wine-making process. (15th May 2018) - Pan, Xinglu; Dong, Fengshou; Liu, Na; Cheng, Youpu; Xu, Jun; Liu, Xingang; Wu, Xiaohu; Chen, Zenglong; Zheng, Yongquan
Highlights: The UHPLC–MS/MS method was used to determine zoxamide enantiomer during wine-making process. The enantioselective dissipation of zoxamide was evaluated during wine making process. Significant enantioselectivity was observed in all three treatment. Peeling process has a significant effect on the reduction of zoxamide. The PFs on the enantiomers of zoxamide were investigated in wine during home processing. Abstract: The fate of zoxamide and its enantiomers were evaluated in detail during wine-making process. The enantiomers of zoxamide were separated and determined by ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC–MS/MS) after each processing procedure including washing, peeling, fermentation and clarification. Significant enantioselectivity was observed in all three treatments with the half-lives of R -zoxamide and S -zoxamide estimated to be 45.6 and 52.9 h in Group A, 45.0 and 52.1 h in Group B, 56.8 and 70.7 h in Group C, respectively. The results indicated that R -zoxamide degraded faster than S -zoxamide during the fermentation process. The processing factors (PFs) of each procedure were generally less than 1, and the PF of the overall process ranged from 0.019 to 0.051, which indicated that the whole process can reduce the zoxamide residue in red and white wine obviously. The results could help facilitate more accurate risk assessments of zoxamide during wine-making process.